Assessment of business conditions benevolence: case of occupational safety and health services - Tunčikienė, Živilė; Drejeris, Rolandas (Journal of Business Economics and Management, 2017)
The aim of the article is to find solutions for assessing the benevolence of business conditions in existing circumstances. The business situation in the area of occupational safety and health (OSH) services was investigated in order to assess possibilities to start up this kind of commercial activity. The proposed methodology of assessment is tested only on the basis of occupational safety and health services, but the sequence and the content of the provided actions for assessment may be also used for initiating any other kinds of business. Systematic approach has been applied to searching for solutions primarily to assess general aspects which are then narrowed down to the assessment of smaller issues. Suitability of theoretical decisions has been tested in real business conditions. In order to assess the benevolence of business conditions in the current situation before starting up a certain business, the article provides certain assessment measures and their application techniques. Applying the chosen methodology may help to start a new business smoother, develop the existing one and thus achieve better results.